The Conservatism of Emoji - Stark, Luke; Crawford, Kate (The New Inquiry, 2014)
The world will soon have its first emoji-only social network: Emoj.li. This news, announced in late June, was met with a combination of scorn and amusement from the tech press. It was seen as another entry in the gimmick-social-network category, to be filed alongside Yo. Yet emoji have a rich and complex history behind the campy shtick: From the rise of the smiley in the second half of the 20th century, emoji emerged out of corporate strategies, copyright claims, and standards disputes to become a ubiquitous digital shorthand. And in their own, highly compressed lexicon, emoji are trying to tell us something about the nature of feelings, of labor, and the new horizons of capitalism. They are the signs of our times.